Proteomic profiling reveals DNA damage, nucleolar and ribosomal stress are the main responses to oxaliplatin treatment in cancer cells - Ozdian, Tomas; Holub, Dusan; Maceckova, Zuzana; Varanasi, Lakshman; Rylova, Gabriela; Rehulka, Jiri; Vaclavkova, Jana; Slavik, Hanus; Moudry, Pavel; Znojek, Pawel; Stankova, Jarmila; de Sanctis, Juan Bautista; et al. (Journal of proteomics, 2017)
UNLABELLED: Oxaliplatin is widely used to treat colorectal cancer in both palliative and adjuvant settings. It is also being tested for use in treating hematological, esophageal, biliary tract, pancreatic, gastric, and hepatocellular cancers. Despite its routine clinical use, little is known about the responses it induces in cancer cells. Therefore the whole-cell proteomics study was conducted to characterize the cellular response induced by oxaliplatin. Chemosensitive CCRF-CEM cells were treated with oxaliplatin at 29.3μM (5×IC50) for 240min (half-time to caspase activation). The proteomes of un-/treated cells were then compared by high-resolution mass spectrometry, revealing 4049 proteins expressed over 3 biological replicates. Among these proteins, 76 were significantly downregulated and 31 significantly upregulated in at least two replicates. In agreement with the DNA-damaging effects of platinum drugs, proteins involved in DNA damage responses were present in both the upregulated and downregulated groups. The downregulated proteins were divided into three subgroups; i) centrosomal proteins, ii) RNA processing and iii) ribosomal proteins, which indicates nucleolar and ribosomal stress. In conclusion, our data supported by further validation experiments indicate the initial cellular response to oxaliplatin is the activation of DNA damage response, which in turn or in parallel triggers nucleolar and ribosomal stress. BIOLOGICAL SIGNIFICANCE: We have performed a whole-cell proteomic study of cellular response to oxaliplatin treatment, which is the drug predominantly used in the treatment of colorectal cancer. Compared to its predecessors, cisplatin and carboplatin, there is only a small fraction of studies dedicated to oxaliplatin. From those studies, most of them are focused on modification of treatment regimens or study of oxaliplatin in new cancer diagnoses. Cellular response hasn't been studied deeply and to our best knowledge, this is the first whole-cell proteomics study focused exclusively to this important topic, which can help to understand molecular mechanisms of action.
Keywords: proteom; fyziologický stres; Humans; Tumor Cells, Cultured; Proteomics; ribozomy; Antineoplastic Agents; lidé; Cell Nucleolus; Nucleolar stress; proteomika; oxaliplatin; Ribosomes; nádorové buňky kultivované; Stress, Physiological; Oxaliplatin; LC-MS; stanovení celkové genové exprese; Neoplasms; protinádorové látky; nádory; poškození DNA; DNA Damage; Ribosomal stress; Proteome; organoplatinové sloučeniny; Gene Expression Profiling; Organoplatinum Compounds; buněčné jadérko